Identification and Phylogenetic Analysis of a Novel Starch Synthase in Maize - Liu, Hanmei; Yu, Guiling; Wei, Bin; Wang, Yongbin; Zhang, Junjie; Hu, Yufeng; Liu, Yinghong; Yu, Guowu; Zhang, Huaiyu; Huang, Yubi (Frontiers in Plant Science, 2015)
Starch is an important reserve of carbon and energy in plants, providing the majority of calories in the human diet and animal feed. Its synthesis is orchestrated by several key enzymes, and the amount and structure of starch, affecting crop yield and quality, are determined mainly by starch synthase (SS) activity. To date, five SS isoforms, including SSI-IV and Granule Bound Starch Synthase (GBSS) have been identified and their physiological functions have been well characterized. Here, we report the identification of a new SS isoform in maize, designated SSV. By searching sequenced genomes, SSV has been found in all green plants with conserved sequences and gene structures. Our phylogenetic analysis based on 780 base pairs has suggested that SSIV and SSV resulted from a gene duplication event, which may have occurred before the algae formation. An expression profile analysis of SSV in maize has indicated that ZmSSV is mainly transcribed in the kernel and ear leaf during the grain filling stage, which is partly similar to other SS isoforms. Therefore, it is likely that SSV may play an important role in starch biosynthesis. Subsequent analysis of SSV function may facilitate understanding the mechanism of starch granules formation, number and structure.